Prognostic significance of preoperative osteopenia on outcomes after gastrectomy for gastric cancer. Issue 2 (10th November 2022) - Fukushima, Naoko; Tsuboi, Kazuto; Nyumura, Yuya; Hoshino, Masato; Masuda, Takahiro; Suzuki, Toshimasa; Kajimoto, Tetsuya; Yano, Fumiaki; Eto, Ken
Abstract: Aim: Osteopenia, characterized by low bone mineral density, is a potential prognostic factor for patients with cancer. The aim of this study was to clarify the impact of preoperative osteopenia in patients with gastric cancer (GC) after gastrectomy. Methods: We included 224 patients with GC who underwent gastrectomy between August 2013 and May 2022. Osteopenia was evaluated by measuring the pixel density in the mid‐vertebral core of the 11th thoracic vertebra using computed tomography. Results: Osteopenia was identified in 68 patients (30%). The osteopenia group had significantly worse overall survival (OS) and disease‐free survival (DFS) than the non‐osteopenia group ( P  < .01, P  < .01, respectively). The postoperative hospital stay was significantly longer, and the occurrence of postoperative complications (Clavien‐Dindo grade ≥ III) was significantly higher in the osteopenia group ( P  = .04, P  < .01, respectively). In multivariate analysis, osteopenia ( P  < .01), stage ≥II ( P  < .01), and R1 or R2 curability ( P  < .01) were independent and significant predictors of DFS. Additionally, osteopenia ( P  < .01), intraoperative blood loss ( P  = .04), stage ≥II ( P  < .01), and R1 or R2 curability ( P  < .01) were independent and significant predictors of OS. Conclusion: Preoperative osteopenia was independently associated with a poor prognosis and recurrence in patients who underwent gastrectomy for GC. Abstract : Osteopenia was independently associated with a poor prognosis and recurrence in patients who underwent gastrectomy for gastric cancer. This is the first report to show the impact of osteopenia on the prognosis of gastric cancer and to compare this risk factor with other preoperative systemic inflammatory response markers or sarcopenia.